The Role of Job Characteristics, Organizational Citizenship Behavior, Self-Efficacy in the Relationship to Employee Performance - Juliana; Amelda Pramezwary; Diena M Lemy; Arifin Djakasaputra; Jimmy Muller Hasoloan Situmorang; Sandra Maleachi (International Journal of Social Science and Business, 2022)
Employee productivity is crucial since it forms the basis and guide for every firm. However, the nature and formality of the work organization play a significant role in determining job characteristics, and although they have an impact on other workplace circumstances, changing job characteristics has inherent restrictions. The purpose of this study is to examine the structural relations among job characteristics, organizational citizenship behavior, self-efficacy related employee performance. The samples of this study consist of 351 representatives utilizing a straightforward irregular inspecting procedure and information from respondents utilizing research instruments utilizing on the web surveys. The exploration technique utilized in this study is Structural Equation Modelling examination and information investigation instruments utilizing SmartPLS 3.3.3. Analysis and interpretation of the data indicate that; self-efficacy have a relationship with employee performance, job characteristics have a relationship with employee performance, organizational citizenship behavior have a relationship with employee performance. The implementation of job characteristics, organizational citizenship behavior, and self-efficacy will greatly impact and make a positive contribution to the hotel activities in improving the performance of its employees.